2018
DOI: 10.1590/s0102-865020180010000004
|View full text |Cite
|
Sign up to set email alerts
|

The effects of subcutaneous injection of nicotine on osseointegration of machined and anodized implants in rabbits

Abstract: Purpose: To evaluate the influence of subcutaneous injection nicotine in osseointegration process on different implant surfaces. Methods: Twenty-two male rabbits were distributed into two groups according to the subcutaneous injections: (1) nicotine 3 mg/day/kg and (2) 0.9 % NaCI 3 mL/day/kg, three times a day; subgroups were then designated-machined and anodized implants were placed in the right and left tibia bones, respectively. The animals were submitted euthanasia after periods of eight weeks to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Locally, nicotine causes a significant decrease in flap blood flow and survival via producing vasoconstriction and intravascular thrombosis, in addition to the increase in platelet aggregation and levels of fibrinogen and blood viscosity. Furthermore, nicotine can cause direct endothelial cell damage, impaired cellular protein synthesis, modification of the lipid profile, and disturbed prostaglandin and thromboxane synthesis and/or release [36][37][38][39] .…”
Section: Discussionmentioning
confidence: 99%
“…Locally, nicotine causes a significant decrease in flap blood flow and survival via producing vasoconstriction and intravascular thrombosis, in addition to the increase in platelet aggregation and levels of fibrinogen and blood viscosity. Furthermore, nicotine can cause direct endothelial cell damage, impaired cellular protein synthesis, modification of the lipid profile, and disturbed prostaglandin and thromboxane synthesis and/or release [36][37][38][39] .…”
Section: Discussionmentioning
confidence: 99%
“…Besides direct impairment of tissue oxygenation and decrease of serum concentrations of growth factors, smoking has damaging effects on bone stability by reducing bone mineralization, collagen synthesis and general healing of tibia fractures and open fractures. Smokers have been shown to have lower bone density compared to nonsmokers, while nicotine itself inhibits alkaline phosphatase and collagen production (145) causing an impact on cancellous bone (146,147). Experimental delivery of nicotine through drinking water in a rabbit model, resulted in a decrease in bone stability and radiological callus formation (148).…”
Section: Smokingmentioning
confidence: 99%
“…On the other hand, a preclinical study demonstrated that there was no deleterious effect of nicotine on the osseointegration process. However, the administration of this medication began just after implant placement, and this study design limits the applicability of these findings since patients will not suddenly initiate smoking habits after the surgical procedure if they do not have this habit before the intervention 18 .…”
Section: Discussionmentioning
confidence: 99%